Archaean andesite petrogenesis: Insights from the Grædefjord Supracrustal Belt, southern West Greenland ... - Szilas, Kristoffer; Hoffmann, J. Elis; Scherstén, Anders; Kokfelt, Thomas F.; Münker, Carsten (Columbia University, 2013)
We present new whole-rock major, trace and platinum-group element data, as well as Sm–Nd and Lu–Hf isotope data for meta-volcanic rocks from the Mesoarchaean Grædefjord Supracrustal Belt (GSB), located within the Tasiusarsuaq terrane, southern West Greenland. We also present new in situ zircon U–Pb isotope data (by LA-ICP-MS) for associated felsic rocks. This region has experienced amphibolite to lower granulite facies metamorphism, causing re-equilibration of most mineral phases (including zircon). An intrusive tonalite sheet with a zircon U–Pb age of 2888 ±6.8 Ma, yields a minimum age for the GSB. The Sm–Nd and Lu–Hf isotope data do not provide meaningful isochron ages, but the isotope compositions of the mafic rocks are consistent with the ca. 2970 Ma regional volcanic event, which is documented in previous studies of the Tasiusarsuaq terrane. The major and trace element data suggest a significant crustal contribution in the petrogenesis of andesitic volcanic rocks in the GSB. The trace element variation ...